Knowledge transfer in enterprise information technology support using web-based self-service systems. (2nd February 2006) - Cooper, Vanessa; Lichtenstein, Sharman; Smith, Ross
This paper explores Critical Success Factors (CSFs) in the transfer of after-sales support-oriented knowledge from Information Technology (IT) support organisations to enterprise customers, using Web-based Self-service Systems (WSS). As it appears that best-in-class companies are ahead of the academic work in this area, we approached the topic through an exploratory CSF study of a best-in-class multinational IT services firm and identified 26 CSFs. Key findings from the study indicate that best-in-class IT service organisations may be cognisant of a range of factors relating to supporting customers, but are less aware of what is needed to support their own frontline support agents. Such organisations also lack an understanding of what is needed to provide enterprise support in the later stages of knowledge transfer, where enterprise customers can experience problems attempting to integrate resolutions. The study further showed that many aspects that might be characterised as encompassing socio-technical issues relating to the provision of web-based self-service are still poorly understood.